2008
DOI: 10.1111/j.1744-7917.2008.00245.x
|View full text |Cite
|
Sign up to set email alerts
|

Variations in body melanisation, ovariole number and fecundity in highland and lowland populations of Drosophila melanogaster from the Indian subcontinent

Abstract: We investigated geographical variations in three fitness‐related traits (body melanisation, ovariole number and fecundity) in laboratory‐reared offspring of 10 populations of Drosophila melanogaster. The populations were collected from adjacent lowland and highland localities (∼80–100 km apart) in the tropical as well as subtropical regions (11.15–31.06 °N) covering a linear distance about 3 000 kilometers from south to north on the Indian subcontinent. Persistence of within‐as well as between‐population diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 29 publications
2
33
0
Order By: Relevance
“…An increasing wing or body melanization with increasing altitude or latitude was found earlier in a number of insects (Munjal et al, 1997;Pool & Aquadro, 2007;Rajpurohit et al, 2008). In the present study, we show a parallel pattern for pupal melanization in two related butterfly species, L. hippothoe and L. tityrus.…”
Section: Pupal Melanization and Heat Gain In L Hippothoe And L Tityrussupporting
confidence: 51%
See 1 more Smart Citation
“…An increasing wing or body melanization with increasing altitude or latitude was found earlier in a number of insects (Munjal et al, 1997;Pool & Aquadro, 2007;Rajpurohit et al, 2008). In the present study, we show a parallel pattern for pupal melanization in two related butterfly species, L. hippothoe and L. tityrus.…”
Section: Pupal Melanization and Heat Gain In L Hippothoe And L Tityrussupporting
confidence: 51%
“…Patterns were similar across species, although the difference between lowand high-altitude populations was more pronounced in L. hippothoe. The recurrent pattern of darker phenotypes being associated with cooler environments is strongly indicative of directional thermal selection on pigmentation (Pool & Aquadro, 2007;Rajpurohit et al, 2008). However, most studies investigating variation in pupal melanization were placed within the context of selection for inconspicuousness because pupae are potentially easy targets for visually oriented predators (Wiklund & Sillentullberg, 1985;Ferreira, Garcia & de Araujo, 2006;Jones et al, 2007).…”
Section: Pupal Melanization and Heat Gain In L Hippothoe And L Tityrusmentioning
confidence: 98%
“…More convincing evidence comes from common garden experiments that compare variation among and within populations, the former demonstrating genetic variance for the traits and the latter a trade‐off at the level of the phenotype. Positive phenotypic correlations between melanization and fecundity have been demonstrated in Drosophila melanogaster (Rajpurohit et al ., ) and D. immigrans (Singh et al ., ). These results are clearly at variance with the trade‐off hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…However, average ovariole number in both Ds (15.2) and Ind (24.8) are below the ancestral range, indicating that ovariole number was independently reduced in both of these lineages. To address the possibility that Ind represents a segregating variant of the North American D. melanogaster range, we note that ovariole numbers in Indian populations (Rajpurohit et al, 2008) are, on average, smaller than those in North American populations (Capy et al, 1993). We also counted ovariole number in five additional D. melanogaster strains from North America, and found that their average ovariole numbers were always higher than those for Ind (Table 1).…”
Section: Reduced Ovariole Number Convergently Evolved In Ds and Indmentioning
confidence: 97%